2021
DOI: 10.1038/s41597-021-01086-4
|View full text |Cite
|
Sign up to set email alerts
|

Monthly direct and indirect greenhouse gases emissions from household consumption in the major Japanese cities

Abstract: Urban household consumption contributes substantially to global greenhouse gases (GHGs) emissions. Urban household emissions encompass both direct and indirect emissions, with the former associated with the direct use of fossil fuels and the latter with the emissions embodied in the consumed goods and services. However, there is a lack of consistent and comprehensive datasets outlining in great detail emissions from urban household consumption. To bridge this data gap, we construct an emission inventory of urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Within the urban context, it is essential to identify specific components within cities that should assume responsibility for implementing climate-change mitigation policies to refine the focus on the significance of urban areas 38 40 . According to various previous demonstrations and analyses, household consumption is a vital component of urban emissions 41 43 , and the necessity of decarbonization has become increasingly critical owing to climate-related concerns. Consequently, understanding the nexus between household behavior and the environment is paramount, given that the production and provision of goods and services are chiefly oriented toward fulfilling the ultimate demand of households 19 , 44 – 46 .…”
Section: Background and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Within the urban context, it is essential to identify specific components within cities that should assume responsibility for implementing climate-change mitigation policies to refine the focus on the significance of urban areas 38 40 . According to various previous demonstrations and analyses, household consumption is a vital component of urban emissions 41 43 , and the necessity of decarbonization has become increasingly critical owing to climate-related concerns. Consequently, understanding the nexus between household behavior and the environment is paramount, given that the production and provision of goods and services are chiefly oriented toward fulfilling the ultimate demand of households 19 , 44 – 46 .…”
Section: Background and Summarymentioning
confidence: 99%
“…In our previous research 41 , we analyzed monthly direct and indirect GHG emissions for 51–52 Japanese cities, spanning 2011 to 2015. The dataset encompasses 1,555,512 items, with 1,543,128 items for indirect emissions and 12,384 items for direct emissions, which are publicly accessible via Figshare in the form of 17 Excel files.…”
Section: Background and Summarymentioning
confidence: 99%
“…Considering that Japan is currently experiencing an accelerating depopulation and aging transition 45 , with more population and younger labor increasingly flowing into megacities 46 , 47 , the implementation of emission reduction policies would make limited progress if we relied solely on global and national calls without considering actions at the subnational level (considering the upgraded spatial heterogeneity). Due to the varying industrial activities and technological levels in different regions and the need to understand the spatial characteristics of carbon footprints better, increasing attention has been given to cities in recent years when conducting carbon accounting in Japan 18 , 48 50 . To date, Japan’s subnational carbon accounting has been conducted in certain defined aspects 49 , and the changes in household direct and indirect carbon emissions have been identified in a specific period 17 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies from the residential sector have found that non‐CO 2 GHGs contribute nearly a quarter of the direct emissions of the residential sector in terms of CO 2 eq (Reinders & Blok, 1999). Furthermore, several studies from the residential sector have shown that the direct emissions are generally much lower than indirect emissions, usually accounting for more than 80% of the total sectoral emissions (even when accounting for non‐CO 2 GHGs) (Kanemoto et al., 2020; Long, Jiang, et al., 2021; Zhang, Zhang, et al., 2018).…”
Section: Methodsmentioning
confidence: 99%